2023
DOI: 10.1177/27536386231185602
|View full text |Cite|
|
Sign up to set email alerts
|

Profiling the Australasian paramedicine tertiary academic sector and workforce: A cross-sectional study

Abstract: Introduction In 1994, the first Australasian paramedicine tertiary program commenced as an off-campus offering not required as an entry-to-practice qualification A quarter of a century later, university programs have proliferated with tertiary qualifications becoming mandatory to acquire Australian Health Practitioner Regulation Agency registration. Despite this progression, concerns have been voiced regarding student enrolment volume and sustainability of the paramedicine academic workforce. To date, a census… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 20 publications
(41 reference statements)
0
3
0
Order By: Relevance
“…Although wellestablished in Australia and New Zealand, the tertiary paramedicine education sector continues to be challenged by issues including infrastructure and resourcing, funding, work-integrated learning capacity, research capacity, and sustainability of the paramedicine academic workforce. 25,57 Many of this cluster's research agenda items echo these previously identified challenges. Whilst tertiary qualifications are mandatory to acquire paramedic registration with the Australian Health Practitioner Regulation Agency and a requirement for employment with the majority of Australian and New Zealand ambulance jurisdictions, the research agenda items apply not only to university education but equally to paramedic education and training provided elsewhere.…”
Section: Education and Trainingmentioning
confidence: 94%
See 2 more Smart Citations
“…Although wellestablished in Australia and New Zealand, the tertiary paramedicine education sector continues to be challenged by issues including infrastructure and resourcing, funding, work-integrated learning capacity, research capacity, and sustainability of the paramedicine academic workforce. 25,57 Many of this cluster's research agenda items echo these previously identified challenges. Whilst tertiary qualifications are mandatory to acquire paramedic registration with the Australian Health Practitioner Regulation Agency and a requirement for employment with the majority of Australian and New Zealand ambulance jurisdictions, the research agenda items apply not only to university education but equally to paramedic education and training provided elsewhere.…”
Section: Education and Trainingmentioning
confidence: 94%
“…Over the ensuing two decades, Australian and New Zealand paramedicine has evolved considerably to become a registered health profession with mandated university entry-to-practice education and considerable research capacity. 25 Tertiary paramedicine education programmes are now offered by 20 universities, housing an estimated 161 paramedicine academics of whom approximately 30 have completed Doctoral research training. 25 In 2015, with reference to these two decades of evolution, O'Meara et al 8 argued again for a national Australasian research agenda and proposed a roadmap to achieving it.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation